2009
DOI: 10.1111/j.1574-6968.2009.01537.x
|View full text |Cite
|
Sign up to set email alerts
|

10-Undecanhydroxamic acid, a hydroxamate derivative of the undecanoic acid, has strong antimicrobial activity through a mechanism that limits iron availability

Abstract: Undecanoic acid (UDA) is a fatty acid with significant antimycotic activity. In this work we have synthesized 10-undecanhydroxamic acid, a hydroxamate derivative of the UDA, and tested its antimicrobial activity on different microorganisms. Our results demonstrate that this compound has higher efficacy than UDA against a variety of fungi and bacteria. Analysis of the intracellular concentration of protein involved in iron transport in Salmonella enterica serovar Typhimurium suggests that its antimicrobial effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
(26 reference statements)
1
6
0
Order By: Relevance
“…Undecanoic acid (UDA), a medium-chain fatty acid, is the most fungitoxic in the C 7:0 -C 18:0 series, which has been used in the treatment of dermatophytoses in humans (Ammendola et al 2009;Garg and Muller 1993). Trichophyton rubrum is a cosmopolitan and anthropophilic fungus able to invade keratinized tissue, causing infection in human skin and nails.…”
Section: Introductionmentioning
confidence: 99%
“…Undecanoic acid (UDA), a medium-chain fatty acid, is the most fungitoxic in the C 7:0 -C 18:0 series, which has been used in the treatment of dermatophytoses in humans (Ammendola et al 2009;Garg and Muller 1993). Trichophyton rubrum is a cosmopolitan and anthropophilic fungus able to invade keratinized tissue, causing infection in human skin and nails.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of two singlet peaks for NH and NH 2 at δ 3.88 ppm and δ 7.49 ppm, respectively, revealed the formation of undec-10-ene hydrazide 3. The appearance of singlet signal ranging from δ 7.49 to 10.72 ppm in the synthesized compounds (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) confirmed the presence of NH of hydrazide derivatives. The appearance of singlet signal of CH proton in compounds 5 at δ 7.92 ppm revealed the formation of N=CH bond in the synthesized derivative.…”
Section: Kumari Et Almentioning
confidence: 79%
“…The synthesis of the intermediate (2,3) and target compounds (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) was performed according to reactions outlined in Schemes 1 and 2. A methanolic solution of undecylenic acid 1 was refluxed in the presence of sulfuric acid to yield the methyl ester undecylenic acid (2).…”
Section: Spectral Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Undecylenic monoethanolamide, which is used in the treatment of fungal infections such as dermatophytosis and scalp disease caused by athlete's foot and has antifungal, antibacterial and antiviral properties, is used in antifungal cream. 10‐Undecahydroxamic acid is more effective than undecylenic acid against various fungi and bacteria . In a study on Salmonella enterica servar typhimurium , a mechanism was reported to be effective because it interferes with the growth of salmonella by forming iron and coordination compounds .…”
Section: Fine Chemicalsmentioning
confidence: 99%